THE CLINICAL IMPORTANCE OF TOTAL DRUG MONITORING IN REDUCING THE TOXICITY ASSOCIATED WITH VALPROIC ACID IN EPILEPTIC CHILDREN IN TAIF CITY - Asim Abdurhman S Alghamdi; Saleh Mohammed Saeed Alghamdi; Abdulelah Mohammed Wajdi Abdullah Halawani; Wafa Azmi Rashed Maruf; Khlood Mohammad Krish Al-Sofiani; Ahmad Hamed A Althomali; Mariam Abdullah Abdurhman Alsalmi (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Background: Epilepsy is a group of neurological disorders that are characterized by an epileptic seizure. An epileptic seizure can last for seconds and may last for a longer time of fewer than five minutes. An epileptic seizure may cause physical harm; therefore, its management is necessary. Epilepsy requires long-term epileptic treatment. Children with epilepsy can be managed by valproic acid, which is the very commonly used antiepileptic drug in clinical practice. However, chronic usage of valproic acid is associated with adverse effects, especially among children. These adverse effects involve hepatotoxicity, coagulation disorders, and pancreatitis. Therapeutic drug monitoring (TDM) is effective in adjusting the dosage of the drug to obtain the optimum concentration in order to reduce toxicities associated with the medication.Aim: To investigate the effects of TDM in assessing liver injury associated with valproic acid treatment for epileptic children  . Methods: This study is a cohort study that was conducted on epileptic children treated with valproic acid monotherapy at least one month after using TDM  at the children hospital in Taif. Liver enzymes, serum creatinine, total bilirubin, direct bilirubin, and dose of valproic acid adjusted by TDM were estimated. Statistical analysis was performed using SPSS software version 21.Results: A total of 126 epileptic children were involved in our study; 68 were involved in the TDM group, and 58 were involved in the non-TDM group. There were significant differences between the two groups regarding the mean of AST (P=0.0001), ALT (P=0.048), and total bilirubin (P=0.0001). There was a significant negative association between valproic acid levels determined by TDM and ALT (r=-0.256, P=0.035), whereas the correlation was positive with serum creatinine (r=0.414, P=0.0001). Logistic regression model showed significant association between TDM usage and elevated AST, OR=0.033, 95% CI=0.004-0.2 (P=0.001).Conclusion: TDM has a significant impact in reducing liver injury and maintaining good hepatic function among epileptic children treated with valproic acid. TDM is also can be used to monitor renal function and correct renal injury by adjusting the valproic acid dose.